(untitled) (The Pakistan Development Review, 2020)
This paper empirically investigates the role of institutional framework in promoting bilateral trade through a regional trade agreement (RTA), namely the South Asian Free Trade Area (SAFTA), using an institutions-augmented gravity model. Poisson Pseudo Maximum Likelihood (PPML) estimation technique is used (performed) for a panel of 11 countries over the period 1996-2015. The initial estimation results suggest that this RTA is not effective in promoting regional trade in South Asia. Further empirical analysis reveals that SAFTA contributes significantly to bilateral trade when the impact of institutions is controlled for. The key policy lesson emerging from the analysis is that, given weak institutional structure, a regional agreement may not produce the desired results. Successful trade reforms depend on the institutional framework of the countries involved. Therefore, government should develop institutions to reap the potential benefits of RTAs. Keywords: Institutions, Regional Integration, Bilateral Trade, South Asia, PPML